Utilization Of Nutrition Services Provided At Health Facilities For Pregnant Women In Moshi – Urban, Kilimanjaro, Tanzania. A Cross Sectional Study - Alex G. Meela; Kissa Kulwa (International Journal of Global Health, 2023)
Nutrition during pregnancy is of utmost important to ensure positive pregnancy outcomes after delivery. This study examined the utilization of nutrition services provided at health facilities to pregnant women. A cross sectional study design, involving 105 pregnant women and 5 RCH providers from 2 health facilities was used. Structured questionnaires, and structured observations were used in data collection. SPSS software version 25 was used in data analysis. Results showed that, RCH providers had inadequate nutrition knowledge due to limited nutrition courses during nursing training and on job trainings/seminars. All RCH providers advised that, nutrition knowledge is important to pregnant women hence they were responsible for its delivery. In adequate staff and lack of teaching materials contributed to the poor delivery of quality nutrition education to all pregnant women as it was observed that there is variations in nutrition information given to women. More than a half of all pregnant women (63%) started their ANC clinic during their first trimester where they received all nutrition services including education on importance of nutrition during pregnancy which helped them to be aware of the relationship between diet maternal nutrition and birth outcomes (63.8%). Most common food group that has been consumed more by pregnant women was grains, roots and tubers and plantains, while also there was high consumption of fruits and vegetables by all women as they are being more emphasized during routine clinics to prevent anemia. Also, there are some barriers that were identified by the service providers which makes their work difficult such as inadequate teaching materials like brochures, posters and jobs aids, also shortage of staff was found to be the core cause of services being provided occasionally as it is the RCH nurse who provide the education and counselling as there is no any nutritionist hired by government at the facility. Regional and district nutrition officers should coordinate and conduct on job training to health providers on issues related to nutrition in order to update their nutrition knowledge and facilitate clear, accurate and more evidence based nutrition information delivered.
Keywords: Nutrition